Organizational Science and the NSF: Funding for Mutual Benefit - Jelinek, Mariann; Griffith, Terri L. (Organization Science, 2005)
The National Science Foundation (NSF) is the primary federal agency funding nonmedical research in the United States. However, relatively few organizational researchers consider approaching the agency, despite the funds it has available. It is easy to understand why: The agency has a reputation for preferring “hard science” and quantitative approaches, and there is no obvious home for organizational studies in the agency. NSF programs appear to recognize psychological and small-group research on the one hand, and sociological research on the other, with little emphasis on organizations. There are, however, several programs that have funded research on organizations, or relevant to organizations. Additionally, the NSF regularly solicits advice and direction from researchers on new directions for focus and attention. We argue that organization researchers should indeed approach NSF with robust research proposals. We provide suggestions for finding an appropriate application “home” within NSF. We also discuss the process of proposal preparation, offering suggestions on how to prepare a persuasive proposal, with comments on how the review process works. Finally, we close with a clarion call for organization researchers to help NSF understand the importance of organizations, and thus of organization research, to the whole array of the agency’s other research interests—to the effective practice of science; to organizing human activity, including economic and educational activity; and to management and governance of human activities in general. As such, we argue, NSF has a stake in organizational research—and organizational researchers have a stake in NSF.